2015
DOI: 10.1007/s00380-015-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of beta-blocker up-titration in conjunction with cardiac resynchronization therapy in heart failure management

Abstract: Clinical practice guidelines emphasize that optimal pharmacotherapy, including beta-blockers (BB), is a prerequisite before receiving cardiac resynchronization therapy (CRT) in eligible patients with heart failure (HF). However, the optimal dose of BB before CRT implantation cannot be tolerated in a number of patients. Sixty-three consecutive patients who underwent CRT in 2006-2013 were retrospectively investigated. Before receiving CRT, BB could not be introduced in 20 patients (32 %); the daily carvedilol-eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Longer period of hospitalization, lower SBP at admission, higher BNP, lower CCr and % β-blockers were also associated with 2-year mortality, as shown in Table 3 , and these associations were consistent with previous reports [ 7 , 8 , 15 , 21 , 22 ]. Thus, the results indicated that the patients in this study did not represent any specific patient group.…”
Section: Discussionsupporting
confidence: 91%
“…Longer period of hospitalization, lower SBP at admission, higher BNP, lower CCr and % β-blockers were also associated with 2-year mortality, as shown in Table 3 , and these associations were consistent with previous reports [ 7 , 8 , 15 , 21 , 22 ]. Thus, the results indicated that the patients in this study did not represent any specific patient group.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the discrepancy of therapeutic effect between high and low pacing proportion group could be attributed to high His-Purkinje system pacing proportion itself. Previous studies demonstrated that increasing the dose of β-blockers was an independent factor to improve the prognosis of HF patients treated with CRT 17 . In the present study, β-blockers dosage (59.9±52.1mg daily) in high pacing proportion group was significantly lower than that (120.6±68.5mg daily) in low pacing proportion group (P = 0.018), indicating that the clinical benefits of patients in high pacing proportion group were further ascribed to the higher pacing proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a combination of early coadministration of BB–ivabradine for patients with acute HF with reduced ejection fraction showed 1-year improvement in LV systolic function 24. Nevertheless, recent data have highlighted that uptitration of HF medication is still a major drawback in real-world practice, and several studies have shown a general effort toward optimization of therapy after CRT with important benefits in reducing HF hospitalization and increasing survival, with a special focus on BB uptitration as an independent predictor of improved HF prognosis 2528. Although such medications as ACE inhibitors/ARBs, loop diuretics, and antialdosteronics are of utmost importance in HF patients and changes pertaining to these drugs were also performed in our cohort during follow-up according to functional status and clinical/paraclinical variables, this study aimed to assess the importance of BB/ivabradine therapy and CRT-device reprogramming after systematic ET in maintaining constant CRT fusion pacing, which has proven to be a real need in clinical practice.…”
Section: Discussionmentioning
confidence: 99%